Fostering the Inclusion of Disadvantaged and Vulnerable Individuals or Groups in Project-Level Grievance Mechanisms - World Bank (Washington, DC : World Bank, 2022)
Principles that are especially relevant to the operation of GMs include: (i) Equality and nondiscrimination. GMs should be easily accessible to all without distinction, although this is not always the case, e.g., if lodging a grievance requires technology that is not universally available or if grievance boxes are not fairly distributed throughout the project area; (ii) Participation and inclusion. GMs require a high degree of participation by stakeholders; (iii) Accountability and the rule of law. Because the purpose of a GM is to ensure that relevant authorities are answerable for their actions and decisions as well as to provide aggrieved persons the opportunity to instigate proceedings for appropriate redress, accountability and the rule of law are crucial.